Journalists in Newsrooms: Professional Roles, Influences, and Changes to Journalism - Sonia Virgínia Moreira; Martín Oller Alonso (Brazilian Journalism Research, 2018)
This special edition of Brazilian Journalism Research hopes to bring more recognition to journalists by assembling a collection of articles that deal specifically with journalists who work in newsrooms and the journalistic practices from different organizational and institutional environments. In that regard, the dossier also provides writers from Ibero-American countries with a space for their articles on the results from the international comparative study entitled Worlds of Journalism Study, which included data collected by researchers from 67 countries and from newsroom journalists in print, audiovisual and online media. This international comparative project produced articles on Argentina, Portugal, Spain and, to a large extent, the experience of the organizers of this dossier and their work coordinating the project in Brazil and Ecuador.